Literatur Review: Analisis Etika dan Kode Etik Profesi Akuntan Dalam Praktik Perpajakan - annisa puteeri ilham; Icha Nurfadhilla; Yustin Giftiani; Naiya Aulia Putri; Agustiawan Agustiawan (Politeknik Negeri Padang, 2025)
Tax accountants have a responsibility to ensure that the tax liabilities reported are accurate and in accordance with applicable regulations. This responsibility includes presenting correct and complete information, as well as avoiding fraudulent practices. To maintain public trust, tax accountants need to improve their professional competence and comply with the applicable code of ethics. This study aims to analyze ethical behavior and the application of the code of ethics in the practice of tax accountants. The method used in this study is qualitative descriptive with a systematic literature review approach. The results of the study show that tax accountants who adhere to the code of ethics can increase public trust in their profession. With the right understanding and application of the code of ethics, the behavior of tax accountants can become more ethical, thereby supporting the creation of good tax governance and increasing public compliance with tax obligations.